La gimnasia cerebral en la psicomotricidad de los niños de 5 a 6 años del subnivel de Educación Preparatoria de la Unidad Educativa "Internacional Cotopaxi", año lectivo 2018-2019. - Pazmiño Gavilanes, María Cleofe (2020)
The present investigation has raised as a problem, the insufficient development of psychomotricity that is reflected with more intensity in preschool children, with difficulties in developing skills such as coordination, laterality, and body schema and spatio temporal alterations. To solve the problem, the general objective of the research was set: To develop a didactic play strategy "Learning with movements", a proposal to promote brain gymnastics for the improvement of psychomotricity in boys and girls from 5 to 6 years of age. Educational Unit "International Cotopaxi", with activities related to play, movement and joy. The methodology that was carried out in the accomplishment of the present work, was directed in the mixed approach of investigation and from this referent, theoretical, empirical methods and investigation techniques were used that allowed, based on epistemological foundations and state of the art, a cultural historical analysis; Furthermore, given the conditions and characteristics of the problem under investigation, it theoretically and methodologically based the strategic proposal, which was endorsed by the criteria of a group of specialist and users as a feasible way to evaluate and validate psychomotor development in infants. , with the experience of the proposal and diagnosed the real situation of needs in toddlers of preschool.